Heterosis and combining ability for seed yield and its component traits in Indian mustard (Brassica juncea L.) - Nandita Patiyal,; Ravindra Kumar,; Preeti Bhatia,; Vijay Singh, (Journal of Oilseed Brassica, 2025)
In a randomized block design, 15 F1s from line x tester crossings with a set of 8 parents and one check were raised during winter 2022-2023 and 2023-2024 with the goal of estimating heterosis and combining ability. The analysis of variance revealed that the mean square due to genotypes, parent crosses, and parent’s v/s crosses were significant for all the traits. On the basis of per se performance and estimates of heterosis, the cross IC-342777 × Maya was found to be most promising, followed by IC-538719 × Maya for seed yield/plant. The GCA effects of the parents, IC-589670, were significantly positive for most of the traits. On the other hand, the SCA effects of the IC-342777 × Maya cross combinations were both significantly positive and negative for seed yield/plant